Mr and Mrs Phd and assistant: MICROSCOPIC INVESTIGATIONS ON THE EFFECT OF TEMPERATURE ON ONION SEED CELL DEGRADATION - Boynazarova, Yulduz (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The oil and fat industry is one of the leading sectors of Uzbekistan's food industry. Existing systems in the oil and fat production sector are designed to process large quantities of primarily homogeneous raw materials.